GÊNESE DA IMPRENSA NO MARANHÃO NOS SÉCULOS XIX E XX - Pinheiro, Roseane Arcanjo (2007)
The Brazilian press was late born, 276 years after the start of the American colony occupation by the Portuguese Crown. Investigating the particularities of this process in the Northeast region, there is an intention to rescue the genesis of typographic activities in Maranhão, which milestone is the newspapers O Conciliador do Maranhão that was issued between November 1821 and July 1823. The objective of this is to identify the sociocultural factors that explain the delay of the press in the State. To do so, it was performed a historical research adopting double methodological strategy: a) qualitative: in order to comprehend the circumstances that contributed to delay the arrival of press to the maranhense capital, conditioning the nature of arising journalistic production; b) quantitative: aiming to reconstruct the journalistic profile, the editorial politic and the morphologic structure of the pioneer newspaper, through content analysis of a sample from that periodic.(AU)